Fabrication of biogas production prototypes from cattle manure on smallholder farm into renewable energy in a balanced and sustainable manner. - Thongsri, P.; Pasom, W.; Rupitak, Q.; Srisaikham, S. (International Journal of Agricultural Technology, 2025)
The result showed the amount of biogas which produced by the biogas production prototype, obtained from cattle manure fermentation averaged 0.058±0.02 m3 or 58 L and the monthly average was 1.74 m3. The biogas obtained from this prototype consisted of 2.88% nitrogen (N2), 57.78% methane (CH4), and 39.29% carbon dioxide (CO2). The flame produced resulting by producing biogas revealed a reddish-blue color. The amount of CH4 and biogas were varied to cattle feeds which related to manure property, and climate. The COD was significantly reduced by biogas production. There was a positive correlation between CH4 and chemical compositions in terms of neutral detergent fiber (NDF), cellulose, hemicellulose, total carbohydrate (TCB), non-fiber carbohydrate (NFC), and nitrogen free extract (NFE) of cattle manure. The smallholder farmers in the community of of Ban Noi Chom Sri Mai Village, Sakon Nakhon Province were trained how to use the prototype to produce biogas. It was found that the participants were able to understand the biogas production process. The participants were satisfied with the design and safety system of the biogas production prototype which had a gas storage tank, safety valve, pressure gauge, etc. The community was interested in applying it to other agricultural waste.